2014
DOI: 10.1002/ana.24304
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting miR‐155 restores abnormal microglia and attenuates disease in SOD1 mice

Abstract: OBJECTIVE To investigate miR-155 in the SOD1 mouse model and human sporadic and familial amyotrophic lateral sclerosis (ALS). METHODS Nanostring microRNA, microglia and immune gene profiles, protein mass spectrometry and RNA-seq analyses were measured in spinal cord microglia, splenic monocytes and spinal cord tissue from SOD1 mice and in spinal cord tissue of familial and sporadic ALS. miR-155 was targeted by genetic ablation or by peripheral or centrally administered anti-miR-155 inhibitor in SOD1 mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
291
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(305 citation statements)
references
References 65 publications
11
291
2
1
Order By: Relevance
“…Such loss of homeostatic microglial gene expression in whole tissue could be due to cell loss, leading to decreased proportion of microglial mRNAs. Alternatively, disease progression could also affect microglial phenotype, and a recent study performed on isolated microglia of mutant SOD1 mice observed that mutant SOD1 microglia lost their typical expression patterns with disease progression [7]. However, our in vitro experiments provide an initial proof of concept that microglial survival could be influenced by serotonergic stimulation of the 5-HT 2B R. Further work is required to determine the relative contributions of microglial cell death and altered microglial phenotypes in the observed degenerative phenotype in vivo as well as the importance of monocyte degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such loss of homeostatic microglial gene expression in whole tissue could be due to cell loss, leading to decreased proportion of microglial mRNAs. Alternatively, disease progression could also affect microglial phenotype, and a recent study performed on isolated microglia of mutant SOD1 mice observed that mutant SOD1 microglia lost their typical expression patterns with disease progression [7]. However, our in vitro experiments provide an initial proof of concept that microglial survival could be influenced by serotonergic stimulation of the 5-HT 2B R. Further work is required to determine the relative contributions of microglial cell death and altered microglial phenotypes in the observed degenerative phenotype in vivo as well as the importance of monocyte degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…5c), suggesting that the loss of Htr2b was associated with degeneration of mononuclear phagocytes in end stage SOD1(G86R) mice. To determine whether this degeneration of mononuclear phagocytes affected microglia and/or monocytes, we measured expression levels of genes known to be part of the homeostatic microglial signature [12,8,9,7], in particular Cx3cr1, Hexb, Tmem119, P2ry12, Olflm3 and SiglecH. All these genes displayed lower expression in SOD1(G86R) mice lacking the Htr2b gene than in SOD1(G86R) mice with the Htr2b gene (Fig.…”
Section: -Ht 2b Receptor Improves Microglial Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…An ASO generated against miR-155 was then shown to prolong survival (by 7%) and prolong disease duration (by 38%) when injected intraventricularly after disease onset [41]. Similar slowing of disease in SOD1G93A mice and prolongation of survival (by 8%) was achieved by a second group inhibiting miR-155 [42].…”
mentioning
confidence: 83%